Project work as a vehicle for information literacy education in disadvantaged schools : an ethnographic field study of grade seven project work in a primary school in Cape Town - Hart, Genevieve Claire (Library and Information Studies Centre (LISC), 2015)
Bibliography: leaves 216-228.